The real impacts of third-party certification on green bond issuances: Evidence from the Chinese green bond market - Yu, Qing; Hui, Eddie Chi-Man; Shen, Jianfu (Journal of Corporate Finance, 2024)
This study examines the real effects of third-party certification on green bond issuance by Chinese listed firms over the period 2016–2022. Our findings reveal that the issuance of certified (non-certified) green bonds results in favourable (non-significant or even negative) stock market reactions in both the short and long term, indicating that third-party certification adds value for stock investors. In addition, we analyse the underlying mechanisms that drive the value creation of third-party certification in green bond issuance. We find that third-party certification effectively reduces information asymmetries between firms and investors, induces firms to genuinely prioritise sustainable practices and improves firms' environmental performance, leading to increases in investor demand and firm value. Our further analysis reveals that third-party certification helps green bond issuers attract long-term investors, increases analyst coverage and induces positive opinions from the regulator on firm disclosure. Overall, this study documents that third-party certification of green bond issuers can generate real economic and environmental benefits for issuers.